PENGGUNAAN APLIKASI PERPUSTAKAAN DIGITAL ISOLOKKAB LEWAT SMARTPHONE - Fitra Ayu, Yun (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
This research is a preliminary study that aims to understand the use of the iSolokKab application in Solok Regency, West Sumatra Province. iSolokKab is a digital library available through an e-book application that can be downloaded online through the Play Store. This study aims to explore the accessibility and usability of the iSolokKab digital library in improving community knowledge, as well as identify factors that hinder its use. The data collection method involved observation and interviews with the community regarding the use of the iSolokKab application. The analysis was conducted descriptively qualitatively. The results showed that socialization related to the availability of this digital library has not been optimal, especially in the aspect of openness. In addition, assistance from library managers is needed to facilitate a better understanding of the iSolokKab application, given that there are still technical obstacles faced by users. Factors inhibiting the use of iSolokKab include internet network problems, incomplete digital collections, eye fatigue, lack of socialization, and user ignorance in solving problems when using the application. Nevertheless, iSolokKab can be accessed through common devices such as smartphones and tablets, and requires a stable internet connection. The iSolokKab digital library has great potential to improve information access and